Adoption and Use of Digital Marketing Tools Among Food and Beverage MSMEs in Gen Z - Dhiani Aprilianti; Aryanti Agustian; Umi Narimawati (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
This study examines the adoption of digital marketing applications by food and beverage Micro, Small, and Medium Enterprises (MSMEs) in Indonesia, specifically targeting Generation Z consumers. The objectives include identifying internal and external factors influencing digital adoption, understanding Gen Z digital behavior and its impact on MSME marketing strategies, exploring the forces and drivers of sustained digital engagement, and promoting a framework linking MSME capabilities, digital platform features, and Gen Z expectations. Using qualitative, literature-based descriptive research, this study reviewed relevant publications covering the years 2018 to 2025. Findings indicate that although MSMEs are increasingly using platforms such as Instagram, TikTok, and WhatsApp Business, they often face challenges such as limited digital skills, time constraints, and financial resources. Gen Z's demand for personalized, fast, and interactive content forces MSMEs to adapt their marketing strategies through storytelling, influencer engagement, and peer-driven content. However, inconsistent use and a lack of strategic planning remain significant barriers. This study advances the digital entrepreneurship literature by examining the relationship between MSME behavior and Gen Z digital culture and provides practical insights for MSMEs and policymakers.